Signaling valuable human capital - Grimpe, Christoph; Kaiser, Ulrich; Sofka, Wolfgang (Strategic Management Journal, 2019)
[Research Summary: The ability of innovative firms to create and capture value depends on innovations that are quickly and widely adopted. Yet, stakeholder concerns can establish important barriers to diffusion. We study the human capital aspect of this challenge and investigate whether innovative firms pay salary premiums to new hires with work experience from advocacy groups like Transparency International. We integrate strategic human capital with stakeholder theory and suggest that advocacy group experience creates signals for valuable human capital in terms of stakeholder knowledge and legitimacy transfers to innovative firms. Using matched data for 3,562 employees in Denmark, we find that new hires with advocacy group experience enjoy larger salary premiums at technologically leading firms, in occupations with direct stakeholder interaction, and for advocacy group top management. Managerial Summary: Innovation research is increasingly aware of the non-technological factors behind successful innovations. Users, regulators, or public opinion can be benevolent supporters or stingy opponents of innovations. Employees with an understanding of the needs and sensitivities of societal stakeholders should therefore be valuable to innovative firms. We find this to be the case when innovative firms hire employees from advocacy groups representing such stakeholders (e.g., Transparency International). Such employees receive higher salaries than an otherwise comparable reference group. These findings indicate that recruiting needs of innovative firms reward stakeholder experience, not merely technological expertise. They demonstrate how firms can create value in the pursuit of the public interest. Further, advocacy groups emerge as an important career stage allowing individuals to develop credible signals for stakeholder expertise.]